People participating in the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows a group of men and women participating in the 1986 y-Walk. They are walking down Almaden Boulevard. Some of them are wearing tee shirts that read: "Walk for women. YWCA 1986" and some of them are carrying balloons. The woman walking in the middle of the photograph in the third row is Jackye McClure. The street is landscaped with ivy and trees.